A Prospective Analysis of 179 Type 2 Superior Labrum Anterior and Posterior Repairs: Outcomes and Factors Associated With Success and Failure. (April 2013) - Provencher, Matthew T.; McCormick, Frank; Dewing, Christopher; McIntire, Sean; Solomon, Daniel
Background: There is a paucity of type 2 superior labrum anterior and posterior (SLAP) surgical outcomes with prospective data. Purpose: To prospectively analyze the clinical outcomes of the arthroscopic treatment of type 2 SLAP tears in a young, active patient population, and to determine factors associated with treatment success and failure. Study Design: Case-control study; Level of evidence, 3. Methods: Over a 4-year period, 225 patients with a type 2 SLAP tear were prospectively enrolled. Two sports/shoulder-fellowship-trained orthopaedic surgeons performed repairs with suture anchors and a vertical suture construct. Patients were excluded if they underwent any additional repairs, including rotator cuff repair, labrum repair outside of the SLAP region, biceps tenodesis or tenotomy, or distal clavicle excision. Dependent variables were preoperative and postoperative assessments with the American Shoulder and Elbow Surgeons (ASES), Single Assessment Numeric Evaluation (SANE), and Western Ontario Shoulder Instability (WOSI) scores and independent physical examinations. A failure analysis was conducted to determine factors associated with failure: age, mechanism of injury, preoperative outcome scores, and smoking. Failure was defined as revision surgery, mean ASES score below 70, or an inability to return to sports and work duties, which was assessed statistically with the Student t test and stepwise logarithmic regression. Results: There were 179 of 225 patients who completed the follow-up for the study (80%) at a mean of 40.4 months (range, 26-62 months). The mean preoperative scores (WOSI, 54%; SANE, 50%; ASES, 65) improved postoperatively (WOSI, 82%; SANE, 85%; ASES, 88) ( P < .01). The mean postoperative range of motion was 159° of flexion, 151° of abduction, and 51° of external rotation at the side, which was less than the mean preoperative range of motion (164° of flexion, 166° of abduction, and 56° of external rotation at the side). Of the 179 patients, 66 patients (36.8%) met failure criteria. Fifty patients elected revision surgery. Advanced age within the cohort (>36 years) was the only factor associated with a statistically significant increase in the incidence of failure. Those who were deemed failed had a mean age of 39.2 years (range, 29-45 years) versus those who were deemed healed with a mean age of 29.7 years (range, 18-36 years) ( P < .001). The relative risk for failure for patients older than 36 years was 3.45 (95% CI, 2.0-4.9). Conclusion: Arthroscopic SLAP repair provides a clinical and statistically significant improvement in shoulder outcomes. However, a reliable return to the previous activity level is limited; 37% of patients had failure, with a 28% revision rate. Age greater than 36 years was associated with a higher chance of failure. Additional work is necessary to determine the optimal diagnosis, indications, and surgical management for those with SLAP injuries.